Optimization Of Rice Production In Asahan District Using The Goal Programming Method - Noerdiansyah; Rina Filia Sari (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2025)
This research aims to optimize rice production in Asahan Regency using the Goal Programming method. The secondary data analyzed included rice production, land area, labor costs, harvesting costs, and selling prices for the period 2021–2023. The Goal Programming model is designed to minimize production costs by considering the proportion of labor costs (70.66%) and harvesting costs (34% of labor costs). The research results show fluctuations in production, with the highest achievement in 2022 at 89,459.42 tons, revenue of Rp 552.86 billion, and profit of Rp 162.21 billion. The application of the model is able to reduce labor and harvest costs, thereby increasing efficiency. Sensitivity analysis shows selling price as the most influential variable on profit, followed by labor costs and harvesting costs; a price decrease of more than 5% could potentially lower revenue below the threshold. This finding confirms the importance of cost control strategies and price stability in maintaining profitability. This research provides practical contributions to local governments and farmers in formulating food security policies and opens up opportunities for developing multi-commodity models in future research.